SIFAT KIMIA DAN SENSORI SERBUK BERAS HITAM DENGAN VARIASI METODE PEMASAKAN DAN PENAMBAHAN BUBUK KEDELAI - Diksy Zeta Amorta; Nurhidajah Nurhidajah (Universitas Muhammadiyah Semarang, 2020)
Black rice is one of the world's rice varieties, in addition to white rice, brown rice, and brown rice. The content of anthocyanin and its antioxidant activity is greater than other types of rice. Therefore, this research done as one effort to exploit black rice. The general purpose of this study was to determine the levels of anthocyanin, antioxidant activity, sensory properties and determine the best treatment. Cooking methods (roasting and oven) and the addition of soy powder (0, 10gr, 20gr, 30gr, 40gr). This study used a Factorial Completely Randomized Design with anthocyanin and DPPH antioxidant activity. The result of statistical test shows hat cooking method and addition of soybean powder have an effect on anthocyanin content, antioxidant activity and sensory properties. The best treatment was roasting and 10 gr from 10 gr weight of black rice with anthocyanin content 4,67 ppm, antioxidant activity 29,80%, sensory value 2,77 (close to likes) and protein value 14,68% . The value of water content in powdered black rice powder also in accordance with standard water content in powder powder ranges from 3% to 5%.